Swath sonar bathymetry during R/V Heincke cruise HE544 with links to multibeam raw data files - Peter Holler (PANGAEA, 2019)
Multibeam data were collected during R/V Heincke cruise HE544. Data recording was executed in North Sea during systematic profiling. Data are unprocessed and may contain outliers and blunders. Therefore the data should not directly be used for grid calculations and charting projects but need to be edited furthermore. One file contains a measurement period not exceeding ten minutes. The dataset consists of 1129 files in Simrad Multibeam Processing Format (*.all) which are compressed with GZIP to size of 50.0 GB (76.1 GB uncompressed). Simrad data files can be processed using the software packages CARIS HIPS/SIPS or with the open source software package MB-System (https://www.mbari.org/products/research-software/mb-system/).